Evaluation of Air Pollution Tolerance Index (APTI) of Plant Species - Uma Devi Randhi (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
Plants play a very important role in maintaining the ecological balance and mitigating air pollution. Along with developmental activities, air pollution is increasing alarmingly in urban areas. The tolerant species of plants/trees function as pollution sink, therefore several environmental benefits can be desired by planting tolerant plant species in polluted areas. For this purpose, evaluation of plant species concerning their tolerance level to air pollution in the form of an air pollution tolerance index may be essential. The urban forestry and plantation programs will give the best results to mitigate air pollution if they plant tolerant plant species in severely polluted urban and industrial areas, and also they can maintain the air quality, soil fertility, and ecological balance.